TERATOGENIC EFFECTS OF BERGAPTEN, A NEW BOTANICAL PESTICIDE, ON FETUSES OF WHITE MICE - Almahdy A. (Universitas Islam Indonesia, 2006)
ABSTRACTLocal white mice were used to evaluate the toxic and teratogenic effects of various dose levels0.0, 0.5, 1.0, and 1.5 mg/kg body weight of Bergapten on fetuses and pups of pregnant females.The oral administration of the different dose levels of Bergapten on days 6-15 of gestation has notproduced any toxic condition and morphological or skeletal changes in fetuses of mice.Key Word : Bergapten, Teratogenicity, mice.